EU enlargement and Ireland's labour market - Alan Barrett (Institute for the Study of Labor (IZA), 2009)
Ireland, along with Sweden and the UK, allowed full access to its labour market to the citizens of the accession countries when the EU enlarged in May 2004. Given the limited number of countries that opened up and the rapid pace of economic growth in Ireland around 2004, a significant inflow was expected. However, the rate of inflow exceeded all expectations. Based on census information, the number of EU10 nationals living in Ireland grew from around 10,000 in 2002 to 120,000 in 2006. Data on inflows suggests that this number could have reached 200,000 by 2008 or 4.5 percent of the population. The EU10 immigrants have very high employment rates and also have levels of education that are comparable to the native labour force in Ireland. However, they appear to earn considerably less than the native labour force and also to be in lower grade occupations. They have impacted positively on the Irish economy in terms of GNP growth. This is because wages grew more slowing in Ireland than would otherwise have been the case as a result of the labour supply increase brought about by this immigration flow.
urn:nbn:de:101:1-20090720299
Keywords: J61; F22; 330; EU enlargement; EU new member states; Ireland; immigration; Einwanderung; Ausländische Arbeitskräfte; Arbeitsangebot; Lohnstruktur; Irland; EU-Erweiterung; Osteuropa